Analysis of Motivation and How The Students Learn in Pandemic: Analisis Motivasi Dan Cara Belajar Mahasiswa Di Masa Pandemi - Wahyuddin; Maharida; Jusriadi, Edi; Syafaruddin (Universitas Muhammadiyah Sidoarjo, 2020)
This study aimed to analyze and describe the level of learning motivation and students’ learning, as well as the obstacles faced by students in online learning during pandemic. This type of research was a qualitative descriptive study conducted at University of Muhammadiyah Makassar during March-April 2020. The population were 19,810, determining the number of samples with the Slovin formula so that the samples were 724 people. The sampling technique was accidental sampling. The method of collecting data using questionnaires that were distributed through google forms. The data analysis technique was descriptive qualitative to describe the research variables. Findings of the study conclude that: 1) Although the learning obstacles faced by students during the pandemic are quite a lot, but student learning motivation is in the high category with mean score is 4,11. Students’ motivation is seen from the indicators desire to succeed, the need for learning, the expectation of students' aspirations for their future, independent learning because of their own desires, committed to learning, having initiative in learning, and having an optimistic attitude in learning; 2) The way students learn is in the pandemic era in the good category with mean score is 3.51. Students have their own way of learning such as arrange learning schedule, rehearse the learning material, spend time reading books, articles and references, and make a summary of the material that has been discussed; 3) Learning constraints faced by students in the pandemic period are in the high category with mean score is 3.69.